Anti Hoax Movement For Students: Skills Training, Whole Person Education And Technology In Semarang City - Rika Saraswati; Abraham Wahyu Nugroho; Rotumiar Pasaribu (SISFORMA, 2022)
Indonesian children mostly are active users of online social media. However, they are easy to be influenced by false information or fake news (hoax). The spreading of hoax itself has threatened Indonesian principle of unity in diversity and destroyed the capacity building of Indonesian children. In order to prevent the children become the victims or the perpetrators of hoax, the need to give the children knowledge of and the way to identify false information is very important. Giving children the right information is the right of the children that is   guaranteed by Indonesian Children Protection Act 2014. The right of the child to obtain the right information rather than false information must be fulfilled because hoax is rampant in Indonesia. The method used to give this knowledge and skills was undertaken through a service learning program by introducing them about the understanding of hoax, the type of hoax, the legal aspect of hoax, the literacy, and the campaign.  After training the students have obtained more knowledge to identify hoax using the software.